2012
DOI: 10.1590/s0100-204x2012001000016
|View full text |Cite
|
Sign up to set email alerts
|

Associação genética de escores de conformação com características de crescimento em bovinos da raça Angus

Abstract: Resumo -O objetivo deste trabalho foi determinar a associação genética entre escores visuais de conformação e as características de ganho de peso médio diário e de velocidade de crescimento em bovinos da raça Angus à desmama e ao sobreano. Os componentes de covariância foram estimados por modelo animal de análise tetracaracterística, com uso do método de inferência bayesiana, tendo-se assumido o modelo linear para: ganho de peso médio diário do nascimento à desmama (GMD) e da desmama ao sobreano (GMS); e veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study on the genetic association between visual scores showed that the selection for conformity for yearlings (amount of meat as measured by length, body depth, and muscle development) affected characteristics of average daily weight gain or speed of weight gain at weaning and over a year of age (EVERLING et al, 2012).…”
Section: Variable ---------------2014-----------------------------201mentioning
confidence: 99%
“…A study on the genetic association between visual scores showed that the selection for conformity for yearlings (amount of meat as measured by length, body depth, and muscle development) affected characteristics of average daily weight gain or speed of weight gain at weaning and over a year of age (EVERLING et al, 2012).…”
Section: Variable ---------------2014-----------------------------201mentioning
confidence: 99%